Comparative study on the antiherpetic activity of aqueous and ethanolic extracts derived from Cajanus cajan (L.) Millsp. - Zu, Yuangang; Fu, Yujie; Wang, Wei; Wu, Nan; Liu, Wei; Kong, Yu; Schiebel, Hans-Martin; Schwarz, Günther; Schnitzler, Paul; Reichling, Jürgen (Forschende Komplementärmedizin, 2010)
Aqueous and ethanolic extracts of Cajanus cajan (Fabaceae) were examined in vitro for their antiviral activity against herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2).